AN ANXIETY FACED BY STUDENTS IN SPEAKING ENGLISH - Erikson Saragih; Manisha Koilara; Diana Hutabarat; Four Tambunan; Nolawati Bancin (Universitas Negeri Medan, 2019)
Abstract: This research was conducted to find out and understand what problems were the main scourge of students in learning and speaking in English using qualitative research methods. In conducting research, the researcher conducts preparations by asking students to speak in public in English one by one with topics freely chosen by students, then after all students have spoken, researchers conduct interviews with each student regarding their obstacles and problems which are their obstacles. speak English. After the researchers collected the data obtained, the researchers conducted an analysis by classifying the responses of the data obtained into several groups to provide a clearer picture related to the problem at hand. During the research activities, researchers also attended the ongoing activities and collected data through observation and interviews. From the results of the research that has been carried out, researchers found that a common obstacle experienced by many students was an internal problem that is doubt about one's own abilities and shame towards others. This will certainly have an impact on reducing students' speaking ability in English going forward. Keywords: students’ anxiety ; speaking English Abstrak: Penelitian ini dilakukan untuk mengetahui dan memahami masalah apakah yang menjadi momok utama siswa dalam belajar dan berbicara dalam bahasa Inggris menggunakan metode penelitian kualitatif. Dalam melakukan penelitian, peneliti melakukan persiapan dengan meminta siswa berbicara di depan umum dalam bahasa Inggris satu per satu dengan topik yang dipilih secara bebas oleh siswa, kemudian setelah semua siswa berbicara, peneliti melakukan wawancara dengan masing-masing siswa mengenai hambatan dan masalah yang menjadi hambatan mereka. berbicara bahasa Inggris. Setelah para peneliti mengumpulkan data yang diperoleh, para peneliti melakukan analisis dengan mengklasifikasikan tanggapan dari data yang diperoleh menjadi beberapa kelompok untuk memberikan gambaran yang lebih jelas terkait dengan masalah yang dihadapi. Selama kegiatan penelitian, peneliti juga menghadiri kegiatan yang sedang berlangsung dan mengumpulkan data melalui observasi dan wawancara. Dari hasil penelitian yang telah dilakukan, peneliti menemukan bahwa hambatan umum yang dialami oleh banyak siswa adalah masalah internal yang meragukan kemampuan diri sendiri dan rasa malu terhadap orang lain. Ini tentunya akan berdampak pada pengurangan kemampuan berbicara siswa dalam Bahasa Inggris ke depan. Kata Kunci: kecemasan siswa; berbicara bahasa Inggris